We Are Still Here: Living with HIV in the UK. Issue 1 (2nd January 2023) - Flint, Adrian; Günsche, Mareike; Burns, Martin
ABSTRACT: In this article we highlight a number of the ongoing challenges faced by people living with HIV in the UK today (2021). Based on in-depth interviews with 23 respondents drawn from a range of ages, backgrounds and walks of life, we offer an insight into deeply personal experiences of what it means to have HIV. We demonstrate the degree to which, 40 years on from the formal emergence of the HIV pandemic, stigma and related structural violence remain both extremely present and extraordinarily debilitating. In essence, social responses to HIV remain mired in a past age.